Shear performance of a novel demountable steel-concrete bolted connector under static push-out tests. (1st April 2018) - Yang, Fei; Liu, Yuqing; Jiang, Zhibo; Xin, Haohui
Highlights: A novel bolted connector with a short bolt, a long bolt and a coupler is proposed. Push-out tests are implemented on four groups of novel bolted connector specimens. The failure mode of novel bolted connector specimens is that the short bolts are sheared off. The shear performance of novel bolted connectors are investigated. Abstract: Bolted connectors could be an alternative to replace conventional welded headed studs between steel girders and concrete slabs, which may benefit prefabricated construction and replacement of concrete slabs considering the life-cycle design of steel-concrete composite structures. In this paper, a novel steel-concrete bolted connector, consisting of a short bolt, a long bolt and a coupler, is proposed. Compared with other bolted connectors, this bolted connector could render the dismantling of concrete slabs more convenient. To investigate the failure mode and fundamental mechanical behaviour of novel bolted connectors and to compare their shear performance with that of conventional welded headed studs, static push-out tests were implemented on four groups of bolted connector specimens and one group of welded stud specimens. The test results demonstrate that the failure mode of novel bolted connectors is that shanks of short bolts are sheared off directly without local concrete crushing phenomenon under couplers. The shear bearing capacity is about 0.8 times of the tensile strength of short bolts, and the peak slip of the steel-concrete interface grows as the bolt shank diameter increases. The exponential expression which generally describes load-slip curves of welded stud connectors simulates the test load-slip curves of novel bolted connectors well. The clearance between bolt shank and bolt hole has a significant effect on the shear stiffness of novel bolted connectors.